The Effect of Oxymel Syrup on Some Cardiovascular Risk Factors in Overweight and Obese People: A Randomized Controlled Trial Study - Marjan Mahdavi-Roshan; Arsalan Salari; Sogol Emaminejad; Shirin Parvinroo; Asieh Ashouri; Iman Alizadeh (Tehran University of Medical Sciences, 2021)
High blood pressure, diabetes, hyperlipidemia and obesity are risk factors for cardiovascular diseases. With regard to the significant role of a healthy diet in the prevention and even treatment of diseases together with the high cost and side effects of drugs, finding foods effective in the treatment of metabolic disorders has been widely considered. This study aimed to evaluate the effect of oxymel - an Iranian traditional syrup with vinegar base - on cardiovascular risk indicators in obese and overweight people. Candidates were selected based on a set of inclusion criteria and were divided into two groups of control and test. The control group received 250 cc of water, while the test group received 250 cc water containing 30 cc of the oxymel for 30 days. Anthropometric and biochemical indicators were measured at the beginning and end of the study. The results showed that there were no significant changes in the body mass index, waist circumference, hip circumference, waist to hip ratio, HDL, LDL, Triglycerides, systolic and diastolic blood pressure, and blood glucose level. However, weight (P = 0.053) and cholesterol (P = 0.083) decreased relatively significantly in the test group compared to the control group. This study shows that consumption of oxymel has positive cardiovascular effects such as lowering the blood cholesterol level and can contribute to weight loss; however, studies with a larger sample size are recommended.